Advances and challenges to the commercialization of organic–inorganic halide perovskite solar cell technology. (March 2018) - Qiu, Longbin; Ono, Luis K.; Qi, Yabing
Abstract: When transferring photovoltaic technologies from laboratory-scale fabrication to industrial applications, low cost, large area, high throughput, high solar-to-energy power conversion efficiency, long lifetime, and low toxicity are crucial attributes. In recent years, organic–inorganic halide perovskite solar cells have emerged as a promising high-performance, cost-effective solar cell technology. However, most of the best reported efficiencies have been obtained on small active-area devices (∼0.1 cm 2 ). Therefore, development of protocols to industrialize such a technology is of paramount importance. In this article, we review the progress of perovskite solar cells with a particular emphasis on fabrication processes and instrumentation that have scale-up potential. For successful commercialization, the capacity to fabricate large-area modules is essential. Long-term stability is discussed, focusing on lifetime measurement and quantification protocols for commercialization. Cost-performance and life-cycle assessment analysis based on recently reported state-of-the-art perovskite solar cells are discussed. These analyses offer insights regarding required efficiency, module area size, and lifetime, in order for perovskite solar cells to be competitive with existing photovoltaic technologies. Finally, lead toxicity and possible solutions to this issue will be discussed. In the outlook, we outline future research directions based on reported results and trends in the field. Highlights: Large-area perovskite film deposition techniques for industrial production of perovskite solar cells and modules. Stability and device lifetime measurement standards and issues related to commercialization. Toxicity of lead and possible solutions.